Exploitation Of Natural Plant Dyes In Silk Fabrics For Aesthetic Fashion Products - Asiani Abu; Nurhijrah (JAF: Journal of Agricultural and Farming, 2024)
In order to revive the use of natural dyes for silk clothing, it is necessary to develop natural dyes by exploiting natural dye sources from various plants that are abundant in South Sulawesi. The purpose of this study is to qualitatively analyze the colors produced by various plants for dyeing silk fabrics. The research was conducted at the silk production center in Sengkang, Wajo Regency, Sulawesi Province, South Sulawesi from March to May 2016. The data collection methods used in this study were observation in the field, interviews, and documentation. The results showed that many types of plants spread in South Sulawesi can be used as dyes for silk materials. Exploration of Natural Dyes through the process of extracting stems, roots, leaves of flowers or fruits from plants used as coloring materials, through the process The mordanting process is carried out before the Dyeing Process with Natural Dyes so that the absorption of natural dyes against silk materials increases. The fixation process is carried out after the dyeing process with natural dyes so that natural dyes absorbed in silk materials have good fastness. The process of dyeing silk with natural dyes from plants so that it can be further developed.